Clinical outcome of ultrasound-guided atelocollagen injection for patients with partial rotator cuff tear in an outpatient clinic: a preliminary study - Sang Hoon Chae; Jae Yeon Won; Jae Chul Yoo (Clinics in Shoulder and Elbow, 2020)
Background Atelocollagen has been studied for restoration of rotator cuff tendon. In this study, we attempted to evaluate the clinical outcome of ultrasound-guided atelocollagen injection in an outpatient clinic for patients with partial rotator cuff tear. Methods We recruited 42 outpatients who visited our hospital from May 2019 to September 2019. Atelocollagen injection was performed in patients with partial rotator cuff tear diagnosed by magnetic resonance imaging and ultrasound. American Shoulder and Elbow Surgeons (ASES), Constant, Korean Shoulder Score (KSS) and Simple Shoulder Test (SST) scores, and range of motion were assessed before injection and after 2 months. Statistically, we analyzed the clinical results using the Wilcoxon signed-rank test. Results Finally, 15 patients were enrolled for analysis. There was no significant difference between pre- and post-injection in terms of range of motion, ASES (57.0 vs. 60.4), Constant (56.4 vs. 58.9), KSS (64.6 vs. 68.5), and pain-visual analog scale (4.2 vs. 3.7), except function-visual analog scale (F-VAS; 6.3 vs. 7.1) and SST (6.6 vs. 6.9). A significant difference was found in SST (P=0.046) and F-VAS (P=0.009). According to the ultrasound results at 2 months, we found hyperechoic materials in three of seven patients. The most common complication of atelocollagen injection was post-injection pain (53%, 8/15). Conclusions Ultrasound-guided atelocollagen injection for partial rotator cuff tear showed no significant change in terms of clinical outcomes, except for F-vas and SST score. Tendon regeneration was not clear due to the remnants of atelocollagen present at 2-month follow-up ultrasound. There seems to be alarming post-injection pain for 2 to 3 days in the patients who received atelocollagen injection in an outpatient clinic.